2019
DOI: 10.1108/dat-07-2018-0035
|View full text |Cite
|
Sign up to set email alerts
|

Dr Jekyll and Mr Hyde: the strange case of the two selves of clandestine drug users in Scotland

Abstract: Purpose The purpose of this paper is to explore the hidden social worlds of competent clandestine users of drugs controlled within the confines of the UK Misuse of Drugs Act 1971, which now includes NPS substances. The authors explore how and in what way socially competent drug users differ from others who are visible to the authorities as criminals by criminal justice bureaucracies and known to treatment agencies as defined problem drug users. Design/methodology/approach This qualitative research utilises a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…As previous scholars have argued, criminalizing and imprisoning drug users may ultimately be more damaging than the addiction itself (Buchanan, 2004;McPhee et al, 2019a). Wider empirical research has demonstrated that high levels of overcrowding and cell sharing can be predictive of stress, self-harm, and suicide among prisoners (for review, see Molleman & van Ginneken, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As previous scholars have argued, criminalizing and imprisoning drug users may ultimately be more damaging than the addiction itself (Buchanan, 2004;McPhee et al, 2019a). Wider empirical research has demonstrated that high levels of overcrowding and cell sharing can be predictive of stress, self-harm, and suicide among prisoners (for review, see Molleman & van Ginneken, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In wider terms, the policy document, The Road to Recovery (Scottish Government, 2008), released 2 years prior to the emergence of the SPS strategy framework, described drug users as 'economically unproductive' which ultimately stigmatized drug users, including those in treatment (McPhee et al, 2013). As McPhee et al (2019aMcPhee et al ( , 2019b argue, despite the methadone user being classed as 'patient' not 'criminal' in society, dependency on methadone causes 'anger and depression' and also impacts on users' 'cultural integration' and their ability to recover from stigma. Combined with the added stigma of being incarcerated, this may ultimately impact negatively on the types of men who took part in our fieldwork, a clear barrier to recovery and reducing reoffending post-release (Enggist et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certainly, questions of health risks and cognitive enhancement permeate some of these stories, such as Member 2's concern of finding a healthy way to navigate the comedown, or the quest for increased productivity, as expressed by Member 1. However, members' stories are informed by their lived experiences with psychostimulants, which do not necessarily correspond faithfully to more formalisedor staticways of understanding their use (McPhee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%